2018
DOI: 10.18632/oncotarget.24054
|View full text |Cite
|
Sign up to set email alerts
|

Comparasion of elective nodal irradiation and involved-field irradiation in esophageal squamous cell carcinoma: a meta analysis

Abstract: It is still controversial whether radical radiotherapy in patients with esophageal squamous cell carcinoma (ESCC) still requires elective nodal irradiation (ENI), or only involved-field irradiation (IFI). In this study, a meta analysis was used to compare ENI and IFI in the treatment of ESCC, in order to provide guidance for clinical practice. Methods: Literatures on ENI and IFI in treatment of ESCC were retrieved, and the last access was June 30, 2017. A meta analysis was performed to evaluate the advantage a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…Therefore, more prospective studies are needed to validate this finding. In our study, IFI showed significant reductions in the incidence of grade ≥3 AE compared with ENI, which is similar to that reported in most studies ( 45 , 49 , 50 ). Compared with the 3D-CRT and 3D-IMRT–mixed subgroups, there were no differences in the incidence of grade ≥3 AE in the IMRT subgroup, which could be explained by the fact that IMRT may reduce the difference in the incidence rates of grade ≥3 AE between two groups.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Therefore, more prospective studies are needed to validate this finding. In our study, IFI showed significant reductions in the incidence of grade ≥3 AE compared with ENI, which is similar to that reported in most studies ( 45 , 49 , 50 ). Compared with the 3D-CRT and 3D-IMRT–mixed subgroups, there were no differences in the incidence of grade ≥3 AE in the IMRT subgroup, which could be explained by the fact that IMRT may reduce the difference in the incidence rates of grade ≥3 AE between two groups.…”
Section: Discussionsupporting
confidence: 91%
“…( 49 ) and Jing et al. ( 50 ). The databases these two authors searched included the China National Knowledge Infrastructure (CNKI) and Chinese Biomedical Literature Database, without including the Web of Science database, which differed from the databases included in the present study.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Fewer Studies reported that three field lymph node dissection in surgical treatment was effective in reducing the incidence of micrometastasis, and the survival rate and local control rate were significantly increased. Therefore, it is of great significance to appropriately increase the radiation range of radiotherapy to reduce the recurrence rate of lymph nodes [21]. Several prospective and retrospective studies reported that the efficacy of IFI was basically similar to ENI, but adverse events were significantly less than ENI, Compared with ENI, IFI have showed similar efficacy and reduced radiation-induced toxicity [22,23].…”
Section: Discussionmentioning
confidence: 99%